2014
DOI: 10.2147/dmso.s38979
|View full text |Cite
|
Sign up to set email alerts
|

Management of obesity and cardiometabolic risk – role of phentermine/extended release topiramate

Abstract: The US Food and Drug Administration (FDA) recently approved lorcaserin and the combination of phentermine and extended release topiramate (phentermine/topiramate ER) for the treatment of obesity in conjunction with a lifestyle intervention, expanding the therapeutic options for long-term obesity pharmacotherapy, which was previously limited to orlistat. Combination phentermine/topiramate ER is associated with greater weight loss compared to its constituent monotherapy, with a more favorable adverse effect prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Phentermine (2-methyl-1-phenylpropan-2-amine) is a sympathomimetic amine approved by the FDA in 1959 for short-term (≤12 wk) weight management as an adjunct to caloric restriction and lifestyle modifications for obese and overweight individuals with weight-related comorbidities (Sweeting et al, 2014). Phentermine is the most commonly prescribed anti-obesity medication in the United States (Hampp et al, 2013).…”
Section: Pharmacotherapies For Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Phentermine (2-methyl-1-phenylpropan-2-amine) is a sympathomimetic amine approved by the FDA in 1959 for short-term (≤12 wk) weight management as an adjunct to caloric restriction and lifestyle modifications for obese and overweight individuals with weight-related comorbidities (Sweeting et al, 2014). Phentermine is the most commonly prescribed anti-obesity medication in the United States (Hampp et al, 2013).…”
Section: Pharmacotherapies For Obesitymentioning
confidence: 99%
“…The most common adverse events include dry mouth and insomnia (Yanovski and Yanovski, 2014). Serious complications include palpitations, tachycardia and hypertension (Sweeting et al, 2014). Long-term, dose-ranging clinical trials are needed to confirm the safety and efficacy of phentermine as an anti-obesity therapeutic.…”
Section: Pharmacotherapies For Obesitymentioning
confidence: 99%
“…In this case, phentermine, diethylpropion, or topiramate may be better options. 13 , 14 , 31 Amphetamine use, due to addictive properties, is not advisable.…”
Section: Special Patient Populationsmentioning
confidence: 99%
“…Indeed, the modes of action of topiramate on energy intake are still poorly understood. However, this novel drug combination is efficacious, showing a weight reduction of approximately 10%, and is regarded as a safe treatment option [ 23 ]. Recently it has been demonstrated that this combination is also able to prevent diabetes in a pre-diabetic population [ 24 , 25 ].…”
Section: Medical Treatment For Obesity – Regulatory Updatementioning
confidence: 99%